Novel design of microgyroscopes employing electrostatic actuation and resistance-change based sensing. (22nd December 2017) - Ghommem, M.; Abdelkefi, A.
Abstract: The nonlinear dynamics of a microgyroscope consisting of a vibrating beam with attached proof mass and operating at high frequency is numerically investigated. The working principle of this inertial sensor is based on exploiting the transfer of the mechanical energy among two vibrations modes via the Coriolis effect to measure the rotation rate. The flexural motion (drive mode) is generated by applying a DC electrostatic load and an AC harmonic load. We propose a novel sensing technique based on resistance change to detect the induced vibrations of the microbeam (sense mode) and extract the rotation rate. The sensing technique is based on transmitting the Coriolis force acting on the proof mass to a probe that affects the resistance of an electrical circuit acting as a variable voltage divider. This is achieved by integrating the probe dipping μ pool (PDP) technology deploying a probe electrode that is dipped into a μ pool filled with a conductive nonvolatile fluid. Large magnitude of the AC harmonic load is observed to give rise to dynamic pull-in bandwidth in the frequency response characterized by large and uncontrollable vibrations of the microbeam. Operating near the primary frequency while selecting moderate AC voltage results in linear calibration curves while maintaining high sensitivity of the output voltage to the change in the rotation speed. The simulation results demonstrate the feasibility of the novel technique for sensing the induced vibrations to deliver measurements of the angular speed. Highlights: Modeling and performance analysis of microgyroscopes. Nonlinear dynamics of electrically-actuated microgyroscopes. Feasibility study of a novel sensing approach based on resistance change. New sensing technique of vibrating beam microgyroscopes.